Long Segment Left Anterior Descending Endarterectomy [10 cm] and its Reconstruction Using Left Internal Thoracic Artery - Suraj Wasudeo Nagre (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2016)
Recently, the use of percutaneous coronary intervention (PCI) for treatment of coronary artery disease has progressively increased. A large number of simple stenoses in one or two coronary vessels can be treated by PCI. Therefore, the number of high-risk and severely diseased patients referred for coronary artery bypass grafting (CABG) has been relatively increasing. Coronary endarterectomy has been used to treat severely or diffusely diseased coronary arteries since the 1950s [1]. More recently, the benefits of endarterectomy for the left anterior descending artery (LAD) have gradually become recognized because surgical techniques and technologies have evolved. The greatest advantage of endarterectomy is that the myocardium supplied by the side branches (diagonal branches and septal perforators) of a diffusely diseased LAD can be relieved of ischemia. This advantage cannot be obtained using a conventional graft to the distal LAD alone because this is beyond the diffusely diseased segments.